Pengaruh Kemudahan, Gaya Hidup Dan Literasi Keuangan Terhadap Keputusan Penggunaan Shopee Paylater Pada Kecamatan Kepanjen - Zaki, Muhammad Firdaus; Basalamah, Muhammad Ridwan; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study seeks to assess how Ease of Use, Lifestyle, and Financial Literacy impact the decision-making process regarding the adoption of Shopee Paylater in the Kepanjen District. With a sample size of 80 respondents determined through Malhotra's formula, data collection involved distributing questionnaires to residents of Kepanjen District selected via purposive sampling. SPSS version 29 was utilized for data analysis, incorporating validity, reliability, normality, and classical assumption tests, along with multiple linear regression analysis, F-tests, T-tests, and coefficient of determination (R2) tests. The findings of this investigation reveal that Ease of Use, Lifestyle, and Financial Literacy significantly and positively influence Usage Decisions. Keywords: Ease of Use, Lifestyle, Financial Literacy, and Usage Decision